Tailoring wo3 Thin Films for Smart Windows: Role of Ar/O2 Ratio in Reactive Sputtering on Film Quality and Electrochromism - Radhalayam, D (ELSEVIER, 2025)
Tungsten oxide (WO3) thin films were deposited on fluorine-doped tin oxide (FTO) and Corning glass (CG) substrates using direct current magnetron sputtering (DCMS) at room temperature. The films were synthesized under varying argon-to-oxygen (Ar:O2) gas flow ratios of 1:1, 2:1, 3:1, 4:1, 5:1, and 6:1 to investigate the influence of sputtering atmosphere on their structural, optical, and electrochromic properties. X-ray diffraction (XRD) analysis confirmed that all films exhibited an amorphous structure, favorable for electrochromic behavior due to improved ion mobility. UV-Vis spectroscopy revealed that optical transmittance varied with gas ratio, peaking at 91 % for the film deposited at an Ar:O2 ratio of 4:1. This suggests enhanced film uniformity and reduced light scattering or absorption at this ratio. Electrochemical analysis showed that the 4:1 ratio also yielded the best electrochromic performance. At an operating voltage window of +/- 0.4 V, the film demonstrated a high coloration efficiency (CE) of 42 cm2/C. Chronoamperometry measurements indicated fast switching behavior with a coloration time of 3.71 s and a bleaching time of 1.71 s. These results emphasize the critical role of gas flow ratio in tailoring the functional characteristics of WO3 films. The optimal 4:1 Ar:O2 ratio offers a balanced combination of high optical transparency, fast response time, and efficient charge usage, making these films highly suitable for electrochromic applications such as smart windows and low-power display technologies.